Globalization and Multi-Polar World in the Aspect of Forensic Activities - I. Je. Nikitina (Теория и практика судебной экспертизы, 2016)
The article considers the trends of improving forensic practice to match the current realities of criminal procedure. It raises issues of international cooperation in terms of forensic support in criminal investigations, including communication and sharing of forensic information. The premises for strengthening international forensic cooperation are outlined, such as globalization in all spheres of human activity, advances in science and technology, including the rapid development of means of communication, and growth in transnational organized crime.